Penerapan Teknologi Tepat Guna/Sasaran Berbasis Energi Terbarukan di Desa Alue Naga Kota Banda Aceh - Ali, Masri; Arif, Zainal; Syahrizal; Dewi, Irma; Nasution, Elvy Sahnur; Ibrahim, Masri; Ali, Nurdin; Machmud, M. Nizar; Husni (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2022)
The focus of community service activities in Alue Naga Village is to provide solutions to the problem of limited electrical energy experienced by the people in Acehr. The purpose of community service is to downstream the results of the author's research on renewable energy technology for the island community. This community service method is (1) Training and technical guidance by the implementing team to partners regarding the operation and maintenance of the appropriate technology system that is applied; (2) the application of appropriate technology based on renewable energy in the form of solar street lights and wind power to increase access to electricity. Through technology transfer in this Community Service activity, it is hoped that the implementation of technology will be maintained continuously; The results of community service are the installation of the application of appropriate technology in the form of solar and wind power and increasing public knowledge about appropriate technology which is carried out through training to community youth partners in Alue Naga Village, Banda Aceh City.